(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
the paper aims to highlight the figure of the notary Macobrius, the presumed assistant of Caffaro and scriptor of his Annales. thanks to the diplomatic and paleographical insights, Macobrius appears to be the material producer of many documents for the genoese Comune in the first half of XIIth Century, and writer of the fragments of a notary protocol (1155-57) contemporary to giovanni’s scriba register.